Understanding Information Effectiveness in Hospitality Accounting Information Systems: Evidence from the Roles of System Quality, Data Accuracy, and AIS Users - Rahel Junita (Golden Ratio of Finance Management, 2026)
Accounting Information Systems (AIS) play an increasingly important role in supporting financial decision making in the hospitality industry, where operational activities require timely and reliable accounting information. However, the effectiveness of accounting information largely depends on the interaction between technological and informational factors. This study examines the effects of AIS users, data accuracy, and system quality on information effectiveness in hospitality organizations in Indonesia. A quantitative research design was employed using a census approach involving 100 accounting and finance employees. Data were collected through structured questionnaires and analyzed using multiple linear regression. The findings reveal that data accuracy and system quality have positive and significant effects on information effectiveness, whereas AIS users do not have a significant direct influence. Simultaneously, all independent variables significantly explain variations in information effectiveness. These findings extend the Information Systems Success Model by emphasizing the strategic importance of data quality and system performance in enhancing accounting information effectiveness within hospitality organizations. Practically, the study suggests that hospitality managers should strengthen data governance, improve system reliability, and continuously optimize AIS implementation to support more effective managerial decision making. This study contributes empirical evidence from an emerging economy and provides insights for future AIS development in the hospitality sector.